Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s10071-023-01751-8
|View full text |Cite
|
Sign up to set email alerts
|

Geckos differentiate self from other using both skin and faecal chemicals: evidence towards self-recognition?

Abstract: Self-recognition is the ability to recognise stimuli originating from oneself. Humans and some non-human animals show evidence of true visual self-recognition in the mirror test. They use their reflection to inspect themselves and to remove a mark that is only visible in the mirror. Not all animals, however, rely primarily on vision. In lizards, chemical cues are crucial in social interactions, and therefore, lizards would benefit from a chemical self-other distinction. Here, we test the tokay gecko (Gekko gec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We also predicted that geckos would show greater responses toward social stimuli, rather than towards the controls, and among social stimuli, less responses towards their own odour, all of which is supported by our results, but most prominently in males. This is likely linked to the information content of the different stimuli, with controls providing the least information, their own odour being very familiar as part of their environment providing no new information (Szabo and Ringler 2023), and the social stimuli giving the most information about potential mating partners. The low response rate towards the peppermint oil control also rules out that novelty was a factor influencing response rates but rather social information encoded in the different social pheromone stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also predicted that geckos would show greater responses toward social stimuli, rather than towards the controls, and among social stimuli, less responses towards their own odour, all of which is supported by our results, but most prominently in males. This is likely linked to the information content of the different stimuli, with controls providing the least information, their own odour being very familiar as part of their environment providing no new information (Szabo and Ringler 2023), and the social stimuli giving the most information about potential mating partners. The low response rate towards the peppermint oil control also rules out that novelty was a factor influencing response rates but rather social information encoded in the different social pheromone stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Using the tongue flick quantification method, studies have shown that some lizards species can discriminate their own odour from that of their conspecifics (e.g. Alberts 1992;Aragón et al 2001;Cooper et al 1999;Mangiacotti et al 2020;Moreira et al 2006;Szabo and Ringler 2023), familiar from unfamiliar conspecifics (e.g. Aragón et al 2001;Font and Desfilis 2002), kin from non-kin (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for self-recognition has been sought in species that are not primarily visual, such as dogs [10], wolves [22] and reptiles [2327], using chemosensory-based self-recognition tests. In these paradigms, subjects are presented with the odour of a substance that originated from themselves (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, olfactory self-recognition studies have found that scent-reliant animals will investigate their marked odour more than their unmarked odour [10,22] or discriminate between self-originating and other-originating skin lipids [25,27]. Burghardt et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, fecal chemicals may proportionate similar or complementary information to femoral gland secretions to female Psammodromus algirus lizards, which can discriminate between young (subadult sneakers) and old (territorial) males based on chemical cues from either femoral secretions or from the feces of males [18]. Tokay geckos (Gekko gecko) can discriminate between their own skin and fecal chemicals, and those of unfamiliar conspecifics of the same sex [19]. However, self-recognition in male Lioalemus tenuis lizards is based on fecal chemicals, but not on precloacal secretions [6].…”
Section: Introductionmentioning
confidence: 99%